2014
DOI: 10.1108/ijcma-12-2012-0091
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles: relationship with conflict management styles

Abstract: Purpose -The purpose of this study is to examine the relationship between leadership styles and conflict management styles among managers, while handling interpersonal conflict (mangers and subordinates). Design/methodology/approach -Middle-level managers (N ϭ 150) from different private sector manufacturing industries were included in the study to seek responses through questionnaire based on instruments for conflict management and leadership styles. Findings -Managers who perceived to exhibit more on transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 21 publications
(24 reference statements)
3
60
0
8
Order By: Relevance
“…Saeed 5 examined the relationship between leadership styles and conflict management styles among managers, while handling interpersonal conflict (mangers and subordinates). Middle-level managers from different private sector manufacturing industries were included.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saeed 5 examined the relationship between leadership styles and conflict management styles among managers, while handling interpersonal conflict (mangers and subordinates). Middle-level managers from different private sector manufacturing industries were included.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Turan et al (2015) found that the first choice of conflict style used by managers who adopt a transformational leadership style is integration. Saeed et al (2014) revealed a positive correlation between transformational leaders and the selection of integration as a conflict management style, along with obligation. Furthermore, Fu et al (2008) concluded that the integrative (collaborative) style of conflict management is the dominant style among transformational leaders.…”
Section: Discussionmentioning
confidence: 99%
“…The findings supported the hypothesis that transformational leadership has a significant diminishing effect on both work stress and employees' negative behaviour. Saeed et al (2014) examined the relationship between the transformational, transactional and laissez-faire leadership styles and conflict management styles. Using a sample of 150 middle managers from private industrial organizations, their results confirmed the hypothesis that the transformational leadership style is positively related to two styles of conflict management: integration and obligation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies conducted to find the relationship between leadership styles and conflict resolution styles emphasized that a strong relationship existed between the two (Kazimoto, 2013;Saeed et al 2014).…”
Section: Leadership Role Perspective and Conflict Resolution Styles Omentioning
confidence: 99%